Learning from clinicians' positive inclination to suicidal patients: A grounded theory model. Issue 2 (7th February 2022) - Soulié, Tess; Levack, William; Jenkin, Gabrielle; Collings, Sunny; Bell, Elliot
Abstract: Despite experts' contention that clinicians' positive inclination is essential to successful treatment of patients at risk for suicide (PRS), research in the area is lacking. This study used grounded theory to develop a model of clinicians' positive inclination based on interviews with 12 clinicians who "liked" working with PRS. The core process identified, a state of emotional synchrony through deep connection between clinicians and PRS, appeared to provide an intersubjective emotion regulation, associated with distress reduction in patients and deep satisfaction in clinicians. Findings suggest clinicians' deep sense of satisfaction and PRS' clinical improvement in treatment could be interdependent.